Improving Indonesian Language Learning Outcomes Through a Cultural Responsive Teaching Approach and the Secret Cards Game Method - Inayah, Putri; Muttaqien, Zedy; Maharani, Desi; Sukmawati, Sukmawati (Lembaga Penelitian dan Pendidikan Mandala, 2024)
This research aims to improve student learning outcomes in Indonesian language subjects using the CRT (Cultural Responsive Teaching) approach and the Secret Cards Game method. This approach is a culture-based approach by linking the material taught. This learning highlights the background and culture that suits the student's profile. The goal is to create fun learning. The subjects of this research were 39 students (18 male students and 21 female students) in class VIII SMP. This classroom action research is reflective and collaborative. The implementation was carried out over two cycles. The results of this research show that the application of the CRT (Cultural Responsive Teaching) approach and the Secret Cards Game method can improve Indonesian language learning outcomes for class VIII SMP students. This can be seen from the increase in the percentage of the average value of observations in cycle 1, namely the completeness value was 55% and the average value was 73%. Of the 39 students, 23 students have achieved the KKM score. Meanwhile, in cycle 2 there was a very good increase with a percentage of 85% and the average value in this cycle reached 87.5%. There were 34 students whose learning outcomes improved. So, using the Cultural Responsive Teaching learning approach and the Secret Cards Game method in learning Indonesian has had an impact on improving the learning outcomes of class VIII students at SMPN 2 Mataram.